Preparation of monolayers of [MnIII 6CrIII]3+ single-molecule magnets on HOPG, mica and silicon surfaces and characterization by means of non-contact AFM - Hoeke Veronika; Krickemeyer Erich; Glaser Thorsten; Derks Christine; Neumann Manfred; Gryzia Aaron; Predatsch Hans; Brechling Armin; Heinzmann Ulrich (Nanoscale Research Letters, 2011)
Abstract We report on the characterization of various salts of [MnIII 6CrIII]3+ complexes prepared on substrates such as highly oriented pyrolytic graphite (HOPG), mica, SiO2, and Si3N4. [MnIII 6CrIII]3+ is a single-molecule magnet, i.e., a superparamagnetic molecule, with a blocking temperature around 2 K. The three positive charges of [MnIII 6CrIII]3+ were electrically neutralized by use of various anions such as tetraphenylborate (BPh4 -), lactate (C3H5O3 -), or perchlorate (ClO4 -). The molecule was prepared on the substrates out of solution using the droplet technique. The main subject of investigation was how the anions and substrates influence the emerging surface topology during and after the preparation. Regarding HOPG and SiO2, flat island-like and hemispheric-shaped structures were created. We observed a strong correlation between the electronic properties of the substrate and the analyzed structures, especially in the case of mica where we observed a gradient in the analyzed structures across the surface.